IMPLEMENTASI KEBIJAKAN TENTANG PENYELENGGARAAN JALAN TOL DI KOTA SEMARANG - Bannu Priyambudi; Herbasuki Nurcahyanto; Slamet Santoso (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
Semarang city is a big city where it has high numbers and high activity of population, so that the public roads become crowded and packed by worker’s vehicle, especially 4 wheel riders which increased every year. Toll roads are roads which are created by the BUMN in coordination with the goverment to reduce the congestion level in major cities, because it is a freeway that uses a charge to use this facility, while for Jasa Marga side who carry out this toll road should be able provide the best service for the users of the highway with the standard operational procedure that have been established.This research was conducted in the city of Semarang. The method used in this research is descriptive-qualitative. The data was collected by using interviews, observation and literature review.This research objective was: first, to find out about the implementation of toll road management in Semarang city, second, to find out the factors that affect the success of toll road implementation.Research outcome shows that: (1) The implementation was conducted according to toll road management guidelines those dictated by BPJT of Jasa Marga central office, the toll road management in Semarang city has been going well, however, there is still some obstacle which hamper the success of this toll road. (2) there’s a unfavorable coordination inside the implementer actor that is Jasa Marga in giving service to the toll road users.Recomendations that author provide: (1) Jasa Marga should provide oversight to every branch towards policies that have been made, should be right on the target of the policies. (2) the need for improvement in every lini and technology so the toll road services become more controlable by the policy implementer side.